2000
DOI: 10.1007/s002800050030
|View full text |Cite
|
Sign up to set email alerts
|

Cisplatin (CDDP) specifically induces apoptosis via sequential activation of caspase-8, -3 and -6 in osteosarcoma

Abstract: This study demonstrates that CDDP specifically induces apoptosis via activation of caspases and the other anticancer drugs induce death of HOS cells via different signaling pathways. It also demonstrates that caspase-8 is a key molecule in the earliest stage of the signaling pathway of CDDP-induced apoptosis of HOS cells, and caspase-3 works downstream of caspase-8.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
74
2
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(84 citation statements)
references
References 32 publications
7
74
2
1
Order By: Relevance
“…Additionally, SNPs used in our association analysis may not have been dense enough to capture all the genotypes in known genes contributing to apoptosis. For example, caspase-6 is involved in the signaling process that determines a cell's fate to live or die and has been shown to induce cisplatin-dependent apoptosis in human osteosarcoma lines [34,37]. This gene is located in the highest LOD score (2.65) region of the linkage scan (on chromosome 4) and may warrant more in-depth analyses.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, SNPs used in our association analysis may not have been dense enough to capture all the genotypes in known genes contributing to apoptosis. For example, caspase-6 is involved in the signaling process that determines a cell's fate to live or die and has been shown to induce cisplatin-dependent apoptosis in human osteosarcoma lines [34,37]. This gene is located in the highest LOD score (2.65) region of the linkage scan (on chromosome 4) and may warrant more in-depth analyses.…”
Section: Discussionmentioning
confidence: 99%
“…Cisplatin is known to induce cell death by activating the apoptosis pathway (Zhang et al 2015;Seki et al 2000), and this constitutes the main mechanism of its antitumor action. In cells that express Hsp70, however, Hsp70 expression has been shown to exert a strongly anti-apoptotic effect (Terauchi et al 2003;Saleh et al 2000).…”
Section: Discussionmentioning
confidence: 99%
“…One mechanism by which CDDP has been proposed to induce apoptosis is through increased expression of the Fas-receptor, a member of the tumour necrosis receptor superfamily, via activation of p53 (Muller et al, 1997;Fulda et al, 1998;Seki et al, 2000). RNase protection analysis demonstrated that pxn65 and pxn100 tumours lacked detectable expression of the Fas-ligand and Fas-receptor and there was no evidence for induction of their expression following CDDP treatment (Figure 4).…”
Section: Analysis Of Apoptotic Gene Expression Following Cddp Treatmementioning
confidence: 99%